2023
DOI: 10.1002/jsfa.12674
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine ameliorates rheumatoid arthritis by regulation of Tfr/Tfh cell balance viatheTLR9‐MyD88‐STAT3 signaling pathway

Abstract: Background Oxymatrine (OMT) is one of the authentic Chinese herbal medicines which has rich and complex active ingredients. however,the relevant potential targets of oxymatrine on rheumatoid arthritis and the mechanism remains unreported. The aim of this study was to determine the regulation of oxymatrine on rheumatoid arthritis using a collagen‐induced arthritis (CIA) mice models and blood samples from RA patients. Results Our results indicated that Tfr cells in RA patients express low levels of Blimp‐1 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Oxymatrine (OMT), an active monomer extracted from various TCMs including Sophora avescens Ait and Radix Sophorae Tonkinensis (Bi et al, 2012, Liang et al, 2023, has demonstrated e cacy in managing chronic hepatitis B (Lu et al, 2004). Besides its hepatoprotective role, OMT exhibits potential against tumorigenesis, in ammation, and bacterial infections (Li et al, 2022, Cao et al, 2023, Zhang et al, 2023a. Notably, in Hepatitis B virus (HBV) transgenic mice liver (Chen et al, 2001), OMT reduces levels of HBsAg and HBcAg, and as a potent immunosuppressant, it curtails replication and in ammation of type A in uenza virus via the TLR4, p38 MAPK, and NF-κB pathways (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxymatrine (OMT), an active monomer extracted from various TCMs including Sophora avescens Ait and Radix Sophorae Tonkinensis (Bi et al, 2012, Liang et al, 2023, has demonstrated e cacy in managing chronic hepatitis B (Lu et al, 2004). Besides its hepatoprotective role, OMT exhibits potential against tumorigenesis, in ammation, and bacterial infections (Li et al, 2022, Cao et al, 2023, Zhang et al, 2023a. Notably, in Hepatitis B virus (HBV) transgenic mice liver (Chen et al, 2001), OMT reduces levels of HBsAg and HBcAg, and as a potent immunosuppressant, it curtails replication and in ammation of type A in uenza virus via the TLR4, p38 MAPK, and NF-κB pathways (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxymatrine (OMT), an active monomer extracted from various TCMs including Sophora avescens Ait and Radix Sophorae Tonkinensis (Bi et al, 2012, Liang et al, 2023, has demonstrated e cacy in managing chronic hepatitis B (Lu et al, 2004). Besides its hepatoprotective role, OMT exhibits potential against tumorigenesis, in ammation, and bacterial infections (Li et al, 2022, Cao et al, 2023, Zhang et al, 2023a. Notably, in Hepatitis B virus (HBV) transgenic mice liver (Chen et al, 2001), OMT reduces levels of HBsAg and HBcAg, and as a potent immunosuppressant, it curtails replication and in ammation of type A in uenza virus via the TLR4, p38 MAPK, and NF-κB pathways (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) offers a distinct perspective on antiviral therapy, emphasizing treatments that are less likely to induce drug resistance. Oxymatrine (OMT), a quinolizidine alkaloid extracted from the roots of Sophora flavescens Aiton and Sophora tonkinensis Gagnep (Fabaceae) [16,17], exhibits a broad spectrum of biological activities [18], including hepatoprotection, anti-tumorigenesis, anti-inflammation, and antibacterial effects [19][20][21]. Its capacity to modulate the immune response and inhibit viral replication of hepatitis B virus (HBV) in transgenic mice underscores its potential as an immunomodulatory agent [22].…”
Section: Introductionmentioning
confidence: 99%